Distribution Deviation Of Limited Over-The-Counter Medicines And Prescription Medicines In Grocery Storesin X Village, Tarakan - Auliyah Sahar; Irma Novrianti; Jufri Ubrusan (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Regarding the distribution of medicines to pharmaceutical facilities, there are several problems that are often found in the community, namely, there are still many places such as grocery stores that do not have permits to sell medicines, in fact quite a few of these stalls sell hard medicines without service and information about good treatment. This research aims to obtain an overview of irregularities in the distribution of restricted over-the-counter medicines including precursors and Obat-Obat Tertentu (OOT) and hard medicines in grocery stores in the amal beach area. This study used descriptive qualitative method. The sample for this research was all grocery stores in the X sub-district area that were willing to be respondents, namely 28 stores. The research results showed that all respondents sold limited over-the-counter drugs including precursors and OOTs as well as hard drugs. The most limited over-the-counter drug sold is Paramex, the most common precursor and oot drug is Mixagrip flu, and the most hard drug is mefenamic acid with various types of brand names. Based on the results of interviews with shop owners, it is known that most drugs are obtained by purchasing directly from pharmacies, sales and drug stores. Based on the results of this research, it can be concluded that there are irregularities in drug distribution in the X Village area, Tarakan City, because there are still grocery stores selling limited over-the-counter drugs, OOT, precursors and hard drugs.